Quality Control in Laboratory - Sarwar Zaman, Gaffar (IntechOpen, 2018)
The book presents a qualitative and quantitative approach to understand, manage and enforce the integration of statistical concepts into quality control and quality assurance methods. Utilizing a sound theoretical and practical foundation and illustrating procedural techniques through scientific examples, this book bridges the gap between statistical quality control, quality assurance and quality management. Detailed procedures have been omitted because of the variety of equipment and commercial kits used in today's clinical laboratories. Instrument manuals and kit package inserts are the most reliable reference for detailed instructions on current analytical procedures.